MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR KEGIATAN EKONOMI MENERAPKAN TEKNIK MODELING PADA SISWA KELAS X SMA NEGERI 1 ABUNG PEKURUN TP 2019/2020 - Sari, Diana (STKIP PGRI Bandar Lampung, 2021)
This study aims to describe the increase in activity and learning achievement of applying Modeling Techniques in Economics subject matter of Economic Activities. The research method is Classroom Action Research (CAR) or classroom action research which is carried out in 3 cycles. The time of the research was carried out in the First Semester of the 2019/2020 Academic Year. The subjects were 30 people. The results showed that the application of learning with modeling techniques could increase the activity and learning achievement of Economic Activities in class X students of SMA Negeri 1 Abung Pekurun, North Lampung 2019/2020 Academic Year.